Velocity-dependent muscle strategy during plantarflexion in humans - Carpentier, A.; Duchateau, J.; Hainaut, K. (Journal of Electromyography and Kinesiology, 1996)
This work examines the relative contribution of the triceps surae heads and the tibialis anterior (TA) to tension development with reference to voluntary plantarflexion at various veloci ties and at two articular positions of the knee joint (extended and flexed at 90"). Subjects were instructed to perform plantarflexion at various submaximal and maximal velocities with no intention of stopping the movement. Voluntary electromyographic (EMG) activity was recorded and the amplitude, duration and integral were analysed. Integrated EMG (IEMG) was normalized with respect to duration. The maximal M wave and the Hoffmann (H) reflex elicited by electrical stimulation of the tibia1 nerve were recorded in the triceps surae to estimate the effects in gastrocnemii (G) length and motoneuron excitability differences, respectively, in the two knee positions. The results indicate that: (a) although the largest EMG activity was recorded in the extended limb, the greatest maximal velocities were performed in the flexed knee position; (b) with increasing velocity of movement, all triceps surae muscles showed enhanced IEMG activities; (c) at a low velocity of movement the soleus (Sol)/G IEMG ratio was larger in the flexed compared to the extended knee; and (d) with increasing velocity, co-activation of agonist and antagonist muscles appeared. It is concluded that the larger maximal velocity of movement observed in the flexed compared to the extended knee was not primarily related to the neural command of the different triceps surae components, but rather to their mechanical properties. Furthermore, co-activation of agonist and antagonist muscles may contribute to the performance of the contractile strategy during rapid movements.